THEORETICAL FOUNDATIONS OF DEVELOPMENT OF PROFESSIONAL AND CREATIVE COMPETENCE OF FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical foundations of the development of the professional-creative competence of future teachers, in particular, the current issues, are studied. Also, theoretical-methodological aspects and tasks for increasing students' creativity were analyzed.